Blood sICAM-1 levels in type 2 diabetes mellitus patients with various grades of DME - S.A. Suk; M. L. Kyryliuk; S. O. Rykov (Ukrainian Society of Ophthalmologists, 2019)
Background: Diabetic macular edema (DME) is a major cause of visual impairment in type 2 diabetes mellitus (DM) patients. Non-specific inflammation is an important factor of the underlying processes of DME. Intercellular adhesion molecules (ICAM), particularly, soluble ICAM-1 (s-ICAM-1), are a local inflammatory mediator involved in the pathogenesis of diabetic injury to the layers of the eye. The literature is scant on the assessment of sICAM-1 blood levels in type 2 DM patients with diabetic injury to the neurovascular system of the eye. Purpose: To investigate serum sICAM-1 levels in type 2 DM patients with various grades of DME. Materials and Methods: Eighty-two type 2 DM patients (145 eyes) were involved in the study; they were divided into four groups based on DME severity. Patients underwent laboratory examination (glycated hemoglobin A1c, HbA1c) and comprehensive eye examination. Inclusion criteria were voluntary informed consent, age above 18 years, and presence of type 2 DM. Exclusion criteria were pregnancy, presence of endocrine disorders that may lead to type 2 DM (Cushing's syndrome, acromegalia, dispituitarism, polycystic ovaries syndrome, etc.), coagulation system impairment, neurodegenerative disorders of the central nervous system, type 1 DM, acute infectious disorders, cancer, decompensation of concomitant medical conditions, mental disorders, administration of neuroleptics and/or antidepressants, or presence of proteinuria, glaucoma or mature cataract. Serum sICAM-1 levels were determined by enzyme-linked immunosorbent assay (ELISA). Single-factor analysis of variance was used for statistical analysis. Results: The median serum sICAM-1 level value for DME0 group (Me = 600.3 ng/mL (593.1 ng/mL - 610.1 ng/mL)) was statistically significantly (p = 0.01) higher than for conventionally amalgamated (DME1 - DME3) group (Me = 558.5 ng/mL (506.9 ng/mL - 607 ng/mL)). Conclusion: The median serum sICAM-1 level value for patients with DME0 (Me = 600.3 ng/mL (593.1 ng/mL - 610.1 ng/mL)) was statistically significantly (p = 0.01) higher than for those with DME1 to DME3 (Me = 558.5 ng/mL (506.9 ng/mL - 607 ng/mL)).